SELECÇÃO DE INVESTIMENTOS EM ACÇÕES PELA ESCOLA FUNDAMENTALISTA: ESTUDO DE CASO CDM E HCB (2021-2023) - Macueve, Belisaria (ALBA - ISFIC Research and Science Journal, 2024)
Investments in the stock market have been associated with uncertainties and great risks, when in fact there are theories that can be learned and assimilated by anyone who wishes to diversify their investments, enhancing results. The general objective of this article was to evaluate the feasibility of the investment from the point of view of the fundamentalist school in the case of CDM and HCB in the periods 2021 to 2023. For this research, a quantitative methodology of a descriptive nature was employed, using the techniques of documentary and bibliographic research for data collection. The results demonstrate that Hidroelétrica de Cahora Bassa (HCB) is the most recommended company for potential investors due to its favorable distribution of resources to its shareholders and its potential for growth when compared to the company Cervejas de Moçambique. The fundamental indicator Dividend Yield reveals that HCB is, therefore, the most attractive company.